(untitled) (Eurasian Journal of Philology Science and Education, 2026)
Today, researching moral and ethical issues is crucial for understanding the role of moral values in society and strengthening them. Due to increasing globalization and cultural exchange, many countries are experiencing changes in their value systems, which calls for a reassessment of ethical principles based on mutual respect and responsibility. Moral and ethical norms are essential for maintaining social order, justice, and peace, which makes their in-depth study one of the pressing issues in modern society. Moral and ethical values in Turkic culture and literature have been formed since ancient times and passed down from generation to generation through folk wisdom, customs, and poetic works. These values are based on concepts such as justice, honesty, patience, kindness, and freedom. Significant works of Turkic literature that reflect moral principles glorify moral ideals through artistic images, didactic teachings, and heroic figures aimed at maintaining stability in society. The examination of Qutb’s “Khosrow and Shirin” in this context is due to the poem’s essential role in promoting spiritual values. This article explores the moral and ethical values in Qutb’s poem “Khosrow and Shirin” and their role in Turkic culture. Qutb’s work, as a medieval example of Kazakh literature, is aimed at preserving and disseminating moral and ethical values. Through the poem’s characters, qualities such as justice, honesty, kindness, love, and spiritual purity are revealed, and their significance in forming the higher stages of morality and culture is analyzed. The poem is also analyzed from a literary and philosophical perspective, highlighting the significance of moral and ethical principles that remain relevant in modern society. Keywords: culture, literature, values, morality, ethics, legacy.